2019
DOI: 10.21608/ejh.2019.6750.1056
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of ectomethrin: A biochemical and histological study

Abstract: Introduction: Ectomethrin (ECM) a synthetic pyrethroid, has broad spectrum use in agriculture, domestic and veterinary medical applications. Its prolonged and indiscriminate use has both acute and chronic toxicity in non-target species including humans. Aim of the work: To evaluate the toxic effects of ECM inhalation in rats, and its recovery after stopping the treatment. Materials and Methods: A total of forty Wistar male albino rats were divided into four groups. First group served as control group and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…However, very few studies have explored the impact of fenpropathrin exposure on cardiovascular physiology. Previous studies have shown that other synthetic pyrethroids like ectomethrin can cause myocardial hypertrophy with elongated hyperchromatic nuclei in rat hearts [ 43 ]. Another study showed that α-cypermethrin, type II pyrethroids, can cause hypertrophic cardiomyocytes and myocardial fibrosis in rats [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies have explored the impact of fenpropathrin exposure on cardiovascular physiology. Previous studies have shown that other synthetic pyrethroids like ectomethrin can cause myocardial hypertrophy with elongated hyperchromatic nuclei in rat hearts [ 43 ]. Another study showed that α-cypermethrin, type II pyrethroids, can cause hypertrophic cardiomyocytes and myocardial fibrosis in rats [ 44 ].…”
Section: Discussionmentioning
confidence: 99%